Histogenesis and histochemical observations on cervix of buffalo during prenatal life - UPPAL, VARINDER; ROY, K S (The Indian Journal of Animal Sciences, 2011)
The study was conducted on cervices of 27 buffalo foetii collected from abattoir at different stages of gestation. The tissues were processed and sections were stained with hematoxylin and eosin, Masson’s trichrome, Gridley’s, Verhoeff,s and Holmes methods. For histochemistry the sections were stained with periodic acid schiff, alcian blue and bromphenol blue for demonstration of neutral mucoploysaccharides, acid mucopolysaccharides and basic proteins.. For lipid demonstration fresh cryostat sections were cut and stained with Sudan Black B and acid hematin. Primary folds of mucosa were observed at 21.0 em CVR (121 days) and secondary at 35.0 em CVR (152 days). Epithelium varied from simple columnar to pseudostratified columnar ciliated. At 13.5 em CVR the cervico vaginal junction was lined by stratified squamous epithelium and extensive cellular mass in the lumen probably represented the part of vaginal plate. The propria submucosa comprised mesenchymal tissue in early fetal life which later on differentiated into different components of connective tissue. At 14.0 cm CVR the bundles of smooth muscles could be observed in tunica muscularis and a serosal layer comprised of differentiating mesenchymal cells and mesothelium could be seen. A moderate to strong reaction of PAS and weak to moderate reaction of Alcian bluelPAS was seen in tunica mucosa, muscularis and serosa in groups 1, 2 and 3. The reaction for basic protein, phospholipids and total lipids was weak to moderate in group I and increased with the progression of fetal age. Â